Bluetooth door lock automation system - Nor Diyana, Hussin (2016)
Smartphones nowadays become a necessity in human life. This era also dubbed as the world's at the fingertips. Therefore, everything can be done by the smartphone. Bluetooth application contained in the smart phone mooted the idea of this project, namely Bluetooth automation door lock system. Previously, to open and close the door houses are done manually where users need to use the key to unlock or lock the door so the probability to lose the key is high and will risk the security of the house. With the development of Bluetooth door lock automation system, the user can unlock and lock their door house with Bluetooth and it is very convenient as people nowadays will always bring the smartphone. This door lock automation system comes with extra secure access. The system can only be accessed and configured by authorized users as it needs to be on the same password with the Bluetooth module in order to access the applications. As long as the user has the smartphone, everybody can afford to have this system as the price is very affordable compare to other door lock in the market.